1996
DOI: 10.1111/j.0022-3646.1996.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

ECOPHYSIOLOGY OF TROPICAL RHODOPHYTES. I. MICROSCALE ACCLIMATION IN PIGMENTATION1,2

Abstract: Microscale pigment adjustments to a tropical photosynthetically active radiation and ultraviolet (UV) environment by the intertidal turf algae Ahnfeltiopsis concinna (J. Ag.) Silva et DeCew and Laurencia mcdermidiae (J. Ag) Abbott were promoted by thalli densities that self‐shade the under story portions of the same diminutive axes. Tissues of A. concinna from canopy microsites had significantly reduced levels of phycoerythrin, phycocyanin, and allophycocyanin compared to tissues from understory microsites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Several factors can lead to algal bleaching and could be responsible for this condition of M. linearis genets in the sheltered transplant site. These include higher irradiance due to lack of shading, potentially lower nitrate levels due to less mixing events during the summer, a disruption of nutrient uptake by higher levels of desiccation, and a thicker blade (Waaland et al 1974, Gerard & Mann 1979, Thomas et al 1987, Gantt 1990, Hurd & Dring 1991, Beach & Smith 1996, Hurd et al 1996. We consider the bleaching of M. linearis to indicate physiological damage, unlike for M. splendens, because M. linearis genets from natural populations do not demonstrate the degree of bleaching demonstrated by M. linearis experimental genets, and bleached individuals of M. linearis in our experiment were more likely to die or lose biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can lead to algal bleaching and could be responsible for this condition of M. linearis genets in the sheltered transplant site. These include higher irradiance due to lack of shading, potentially lower nitrate levels due to less mixing events during the summer, a disruption of nutrient uptake by higher levels of desiccation, and a thicker blade (Waaland et al 1974, Gerard & Mann 1979, Thomas et al 1987, Gantt 1990, Hurd & Dring 1991, Beach & Smith 1996, Hurd et al 1996. We consider the bleaching of M. linearis to indicate physiological damage, unlike for M. splendens, because M. linearis genets from natural populations do not demonstrate the degree of bleaching demonstrated by M. linearis experimental genets, and bleached individuals of M. linearis in our experiment were more likely to die or lose biomass.…”
Section: Discussionmentioning
confidence: 99%
“…They also differ in their ability to cope with enhanced UV radiation [107]. A broad survey was carried out to understand photosynthesis in aquatic ecosystems and the different adaptation strategies to solar radiation of ecologically important species of green, red and brown algae from the North Sea, Baltic Sea, Mediterranean, Atlantic, polar and tropical oceans [26,106,[108][109][110][111][112][113].…”
Section: Macroalgae and Seagrassesmentioning
confidence: 99%
“…Since these substances are chemically very stable, they accumulate in the sediment of lakes and can be used of a permanent record for past ultraviolet radiation environments [131]. In tropical algae, enhanced levels of carotenoids and UV-absorbing compounds were detected in tissues from the canopy compared to tissues from understorey locations in turf-forming rhodophytes [110,111]. Current research indicates that solar UV-B is a stress factor for macroalgae and seagrasses even at current levels; therefore further increases in UV-B may reduce biomass production and changes in species composition in macroalgae ecosystems.…”
Section: Macroalgae and Seagrassesmentioning
confidence: 99%
“…Research on phytochrome‐mediated shade responses in higher plants has shown that plants acclimated under highly crowded, low‐irradiance conditions display significant stem elongation that confers a fitness advantage in a crowded setting compared with plants acclimated to high‐irradiance conditions where crowding is not a problem (Schmitt et al ., 1995; Dudley and Schmitt, 1996). Similarly, marine micro‐ and macroalgae have been shown to precisely regulate photopigment content in response to changes in irradiance (Goldsborough and Kemp, 1988; Villafañe et al ., 1995; Beach and Smith, 1996a; Beach and Smith, 1996b; Helbling et al ., 1996; Robinson et al ., 1997; Vergara et al ., 1998; Zudaire and Roy, 2001). Many of these studies also found an increase in UV‐absorbing pigments (e.g.…”
Section: Introductionmentioning
confidence: 99%